Changes in the timing of hay cutting in Germany do not keep pace with climate warming. (7th August 2013) - Bock, Anna; Sparks, Tim H.; Estrella, Nicole; Menzel, Annette
Abstract A unique long‐term phenological data set of over 110 000 records of 1st cutting dates for haymaking across Germany, spanning the years 1951–2011 was examined. In addition, we analyzed a long‐term data set in the beginning of flowering of meadow foxtail (Alopecurus pratensis) covering the last 20 years. We tested whether hay‐cutting dates (based on a human decision when to cut) showed trends, temperature relationships and spatial distribution similar to the development of this grassland species, and if these trends could be related to climate change. The timing of 1st hay cut was strongly influenced (P < 0.001) by altitude, latitude and longitude, revealing in particular an east‐west gradient. Over the past 60 years, there have been changes in the timing of hay cutting, with the majority of German federal states having significant (P < 0.05) advances of approximately 1 day per decade. Overall, the response to mean March–May temperature was highly significant (−2.87 days °C−1; P < 0.001). However, in the last 20 years, no federal state experienced a significant advance and two were even significantly delayed. The temperature response in this post‐1991 period became less or non‐significant for most of the federal states. We suggest that differences in agricultural land use and unequal uptakes of Agri‐Environment Schemes (AES, which encourage later cutting) were likely to be responsible for the regional differences, while the general increase in AES appears to have confounded the overall trend in hay cutting in the last 20 years. Trends over time and responses to temperature were small relative to those associated with the phenology of meadow foxtail. The advance in phenology of this species is greater than the advance in hay cutting, implying that hay cutting may not be keeping pace with a changing climate, which may have a positive effect on grassland ecology.